Analyzing the effects of applying IoT to a metal-mechanical company - Eduardo Ca\~nizares; Faustino Alarcón Valero (Journal of Industrial Engineering and Management (JIEM), 2018)
Purpose: The purpose of this paper is to show the improvements obtained through the application of IoT in a company of the metal-mechanical sector. Design/methodology/approach: The methodology used has been the collection of data before and after the application of the IoT in the process to manufacture tool-machines. Findings: Improvements obtained in some aspects of the process are very high (above 30%), making it a process that is more efficient allowing reduce costs. Research limitations/implications: Some aspects or details are difficult to quantify because there are no measurable parameters. Practical implications: Technological advances and new technologies applied to the industry, allows significant improvements in production. Social implications: Improvements obtained in the process can improve the conditions of workers. Originality/value: Originality of the paper is very high, because there are no publications of study or practical cases in the sector, due to the confidentiality and competitiveness of the sector.
Keywords: 650; internet of things; industry 4.0; manufacturing; improvement; process; die; tool-ing; stamp; rfid; wi-fi